Unity in Diversity: Federalism in Multiethnic Country Nepal - Rai, Prakash (Prāgyik Prabāha, 2023)
Federalism, in general and multiethnic federalism, in particular is supposed to be a device to create unity in diversity in multiethnic country. Multiethnic federalism, a form of federalism, in which the territorial government or state is carved out based on nation or ethnic category to enable national minorities to exercise indigenous and ethnic minority rights like self-rule and autonomy is supposed to be a device to create unity in diversity in multiethnic country like Nepal. In Nepal, indigenous nationalities, and Madhesi communities who, historically, have been excluded in state’s institutions, have demanded multiethnic federalism, identity-based federalism on their own term, as an institutional device for their inclusion in the state. They have argued that it is a device to generate unity in diversity through accommodating diversity in the state. But there was no consensus on this issue while making the constitution through the constituent assembly. Some have argued that it would be a 'castist' (Jatiya) state if ethnic-based federalism is adopted. In this article, I have argued that multiethnic federalism is a device to end the nature of the age-old exclusionary Nepali state and an institutional mechanism of healing the inter-ethnic rupture of Nepali society. Indigenous nationalities in Nepal have demanded separation within a state to protect and promote their identity based on democratic values rather than separate from a state of their own. For this purpose, I have reviewed theoretical articles and critically analyze how it creates unity in diversity in a multiethnic country like Nepal.